Tingkat Efisiensi Pada Usahatani Padi Sawah di Desa Noelbaki, Kabupaten Kupang, NTT - Johanna Suek; Yosefa Bernadina Nitit Ritan; Sondang Pudjiastuti (Fakultas Pertanian, Universitas Timor, 2021)
Efficiency can be achieved by minimizing the resources needed to produce a particular output, or maximizing the output generated from a particular resource. Efficient use of resources can increase productivity. How efficient is the use of resources in rice paddy farming, invested through studies aimed to estimate production factors that affect rice farming and to measure its efficiency. The research was conducted in Noelbaki Village, Central Kupang District, Kupang Regency. Determination of the population used purposive sampling method, in which with the consideration of farmers who own rice fields. Sample is chosen as random sampling as much as 60 famers from the population. Data is analyzed with Cobb-Douglas stochastic frontier production function, and Cobb-Douglas Stochastic Frontier cost function to obtain economic efficiency value. Allocative efficiency is estimated from rasio between technical efficiency and economic efficiency. The results showed that the factors of land area production, seeds, fertilizers, labor have a significant effect on rice. The use of input factors in rice paddy farming can be said to be quite efficient technically and economically with an average value of 0.81±0,11 and 0.84±0,15, respectively. While the allocative efficiency is very efficient with an average value of 0.99±0,21.